Approach for Machine Health Monitoring System of a Machine - Singh, Dharmendra; Garg, Divyansh; Sharma, Abhishek; R. Mishra, V. (International Journal of Engineering and Technology, 2018)
Vibration monitoring system has become a recognized technique to supervise the maintenance of machine. Machine health monitoring is the process of monitoring the condition of a machine to predict mechanical wear and tear and to predict failure of the machine. Vibration, noise, and temperature parameters are frequently used as key indicators to check the condition of the machines. This piece of study describes here is the development of a Machine Health Monitoring System using the vibration and the temperature of the tool of the machine as machining monitoring parameters. The selection of these parameters are based on the fact that this parameter is mainly responsible for the failure of a machine and also these parameters affect the quality of the part. The restrictions associated in this paper for Condition Based Monitoring are the installation of device on the machine and the cost of the Condition Based Monitoring Device increases with increase in number of measurement parameters, Condition based monitoring system helps in making the strategies to avoid unwanted tragic failure. This paper discusses the machine health monitoring using the vibration and tool temperature as an input parameter for health monitoring.Â Â Â